Complex gel phase change heat storage structure and preparation method thereof
Through 3D printing and freeze-thaw molding technology, combined with high thermally conductive elastomer packaging, the problem of hydrogels being difficult to form complex structures is solved, and the preparation of complex gel phase change heat storage structures is realized, adapting to complex environments and possessing excellent leakage protection performance.
Patent Information
- Application Number
- CN202411801731.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
It is difficult for existing hydrogel materials to form complex three-dimensional structures, and they need to be immersed and restored after water loss, making it difficult to adapt to complex environmental conditions.
The packaging model was prepared by 3D printing, and the PVA aqueous solution containing hydrated inorganic salt was filled with vacuum, and frozen and thawed, and finally secondary packaging was performed with high thermal conductivity elastomer to form a complex gel phase change heat storage structure.
The complex structure formation of hydrogel and excellent leakage resistance are achieved, making it adaptable to complex application scenarios and improving thermal management capabilities.
Smart Images

Figure CN119614159A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage materials, and in particular to a complex gel phase change heat storage structure and a preparation method thereof. Background Art
[0002] The rapid development of human society is accompanied by the problem of excessive consumption of traditional fossil energy such as oil, natural gas, and coal. These energy sources are limited and non-renewable. At the same time, excessive use and waste of energy will inevitably lead to environmental pollution and climate warming. However, in many fields such as industry and people's livelihood, there are often problems of low efficiency in the process of energy conversion and utilization, which need to be solved urgently. In recent years, energy storage technology has developed rapidly, providing an effective way to improve energy utilization.
[0003] Hydrogel is a material with a very high water content and can be solid at room temperature. The water inside it can evaporate freely, so when the surface temperature of an object rises, the hydrogel can significantly reduce the surface temperature of the object, making it an excellent energy storage material.
[0004] However, general hydrogels will continue to lose water and must be immersed in liquid water to restore their original state and work normally. It is also difficult for them to form complex three-dimensional structures, so it is difficult to adapt to complex environmental conditions. Summary of the invention
[0005] In response to the above problems, the present invention provides a complex gel phase change heat storage structure and a preparation method thereof. The method enables the hydrogel to have a complex structure and excellent anti-leakage performance, so that it can adapt to complex application scenarios and be used on the surfaces of various heat source objects.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows: In a first aspect, the present application provides a method for preparing a complex gel phase change heat storage structure, comprising the following steps: Provide packaging model; Filling the PVA aqueous solution containing hydrated inorganic salt into the packaging mold by vacuuming to perform the first packaging; The encapsulated model after the first encapsulation is subjected to freeze-thaw molding to form a PVA hydrogel; Filling a high thermal conductive elastomer onto the surface of the encapsulation model after the PVA hydrogel is formed for secondary encapsulation; After waiting for the high thermal conductivity elastomer to completely solidify, a complex gel phase change heat storage structure is obtained.
[0007] As a further improvement of the present invention, the packaging model provided is a packaging model with a set heat storage structure shape printed by 3D printing, and the filling rate of the packaging model is 18%~22%.
[0008] As a further improvement of the present invention, the material of the packaging model is a printing material doped with a high thermal conductivity material, and the printing material is one or more of PLA, ABS, and nylon; the high thermal conductivity material is one or more of carbon nanotubes, carbon fibers, and graphene.
[0009] As a further improvement of the present invention, the mass fraction of PVA in the PVA aqueous solution is 5% - 20%.
[0010] As a further improvement of the present invention, the hydrated inorganic salt includes one or more of sodium sulfate decahydrate, calcium chloride hexahydrate, and disodium hydrogen sulfate dodecahydrate, and the added amount of the hydrated inorganic salt is the same as that of PVA.
[0011] As a further improvement of the present invention, the freeze-thaw molding of the packaging model after the first packaging includes: The encapsulated model after the first encapsulation was frozen at -18~-25℃ for 8~12 h, thawed at 20~26℃ for 1~3 h, and the freezing and thawing operation was repeated 3 to 7 times until the PVA hydrogel was formed.
[0012] As a further improvement of the present invention, the high thermal conductivity elastomer is silicone rubber doped with a high thermal conductivity material, and the high thermal conductivity material is one or more of metal particles, liquid metal, carbon nanotubes, carbon fibers, and graphene.
[0013] As a further improvement of the present invention, the method of filling the high thermal conductive elastomer into the surface of the encapsulation model after the PVA hydrogel is formed comprises: The silicone rubber and the high thermal conductivity material are fully mixed to form a high thermal conductivity elastomer; before the high thermal conductivity elastomer is cured, the packaging model containing the PVA hydrogel is immersed in the high thermal conductivity elastomer, and the surface of the packaging model is packaged to form a high thermal conductivity elastomer packaging layer.
[0014] As a further improvement of the present invention, the filling rate of the packaging model is variable, the wall thickness of the packaging model is less than 1 mm, and the thickness of the high thermal conductivity elastomer packaging layer is less than 1 mm.
[0015] In a second aspect, the present application provides a complex gel phase change heat storage structure, which is prepared according to the method for preparing a complex gel phase change heat storage structure. Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a complex gel phase change heat storage structure, wherein a hydrogel encapsulation model is obtained by 3D printing, and then a PVA aqueous solution containing a hydrated inorganic salt is filled into the encapsulation model by vacuuming, and then the encapsulation model is freeze-thawed, and finally the surface of the encapsulation model is encapsulated for a second time using a high thermal conductivity elastomer. The present invention enables the hydrogel to have a complex structure, so as to adapt to complex application scenarios, and the hydrogel is double-encapsulated by using an encapsulation model and a high thermal conductivity elastomer, so that it has excellent anti-leakage performance. In addition, the content of the hydrogel in the encapsulation model can be indirectly controlled by adjusting the filling rate of the encapsulation model. The preparation method can prepare a phase change heat storage gel with a complex three-dimensional structure, and the preparation steps are simple and easy. The complex gel phase change heat storage structure is encapsulated by the encapsulation model and the high thermal conductivity elastomer, and can adapt to a variety of harsh and complex working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A schematic diagram of a method for preparing a complex gel phase change heat storage structure; Figure 2 To adopt Figure 1 A complex gel phase change heat storage device prepared by a method; Figure 3 for Figure 2 Top view and cross-section Figure 1 ; (a) is a top view, (b) is an AA section view; Figure 4 for Figure 2 Front view and section view Figure 2 ; (a) is a top view, (b) is a BB cross-sectional view; Figure 5 To verify the temperature control performance change trend diagram of the complex gel phase change heat storage structure. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0018] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0019] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0020] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0021] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an", "the" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0022] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.
[0023] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0024] The first aspect of the embodiment of the present application provides a method for preparing a complex gel phase change heat storage structure, comprising the following steps: S1, provides packaging model; S2, filling the PVA aqueous solution containing hydrated inorganic salt into the packaging model by vacuuming to perform the first packaging; S3, freeze-thaw molding the encapsulated model after the first encapsulation to form a PVA hydrogel; S4, filling a high thermal conductive elastomer into the surface of the encapsulation model after the PVA hydrogel is formed, and performing secondary encapsulation; The first aspect of the present application provides a method for preparing a complex gel phase change heat storage structure. The preparation method first prepares a packaging model. The packaging model with a corresponding shape can be obtained according to a preset complex model of the heat storage structure by using 3D printing technology, etc. This step ensures that the packaging model has the required accuracy and complexity, and provides a basis for subsequent hydrogel filling and encapsulation. Then, the PVA aqueous solution is prepared and filled, and PVA (polyvinyl alcohol) is dissolved in water to prepare a PVA aqueous solution containing a certain concentration of hydrated inorganic salts. The addition of hydrated inorganic salts can improve the heat storage performance and thermal stability of the hydrogel. The PVA aqueous solution containing hydrated inorganic salts is filled into the packaging model by vacuuming. Vacuuming can remove gas and water vapor in the solution, avoid the generation of bubbles, and ensure the uniformity and integrity of the filling. Again, the hydrogel is freeze-thawed, and the packaging model filled with the PVA aqueous solution is frozen to form ice crystals from the water molecules in the solution, thereby achieving the initial solidification of the hydrogel. Subsequently, a thawing treatment is performed to melt and rearrange the ice crystals to form a hydrogel with a stable three-dimensional network structure. This process ensures that the hydrogel has excellent mechanical properties and heat storage properties. Finally, the high thermal conductivity elastomer is secondary packaged to prepare a high thermal conductivity elastomer material, which should have good thermal conductivity and elasticity to ensure that the encapsulated gel phase change heat storage structure can maintain stable performance under various environments. The high thermal conductivity elastomer material is evenly coated on the surface of the encapsulation model for secondary packaging. This step not only improves the overall strength of the structure, but also ensures that heat can be efficiently transferred to the external environment.
[0025] In step S1, a packaging model is provided. Specifically, a solution is to use 3D printing to print a packaging model of a specific heat storage structure shape. The specific shape can be designed according to the specific situation, and this application does not make any specific limitation.
[0026] More specifically, the complex gel phase change heat storage structure includes a packaging model, a hydrogel, and a high thermal conductivity elastomer, wherein: the packaging model is obtained by 3D printing, and then a PVA aqueous solution containing a hydrated inorganic salt is filled into the packaging model by vacuuming to encapsulate the hydrogel for the first time, and then the PVA aqueous solution containing a hydrated inorganic salt is freeze-thawed to form, and finally the surface of the packaging model is secondary encapsulated using a high thermal conductivity elastomer.
[0027] In some embodiments, the packaging model of the present application may be a basic structure corresponding to a specific application, such as a heat storage element, etc. Figures 2 to 4 of complex shapes.
[0028] In some embodiments, the material of the packaging model is a printing material doped with a high thermal conductivity material, and the printing material is one or more of PLA, ABS, and nylon; the high thermal conductivity material is one or more of carbon nanotubes, carbon fibers, and graphene.
[0029] Among them, PLA is derived from renewable resources such as corn starch, is biodegradable, and meets environmental protection requirements. The printing process is smooth and suitable for home and educational environments. ABS material has good impact strength and is suitable for printing workpieces with high strength requirements. It has good heat resistance and can maintain stable performance within a certain temperature range. Nylon material has high strength and toughness and is suitable for printing industrial and aerospace precision parts. It has excellent wear resistance and is suitable for packaging models that require wear resistance.
[0030] As an example, carbon nanotubes have excellent thermal conductivity and can significantly improve the thermal conductivity of the packaging model. Carbon nanotubes can also enhance the mechanical properties of the packaging model to a certain extent. Carbon fiber is light and high in strength, and is suitable for packaging models that require lightweight and high strength. By adjusting the content and arrangement of carbon fiber, the thermal conductivity of the packaging model can be regulated. Graphene also has excellent thermal conductivity and can further improve the thermal conductivity efficiency of the packaging model. The synergistic effect of graphene and other thermal conductive materials (such as carbon nanotubes and carbon fibers) can significantly reduce the interface thermal resistance and improve the overall thermal conductivity.
[0031] In some embodiments, through 3D printing technology, the printed packaging model can be customized according to actual needs to meet personalized and customized needs. Printing materials doped with high thermal conductivity materials can significantly improve the heat dissipation efficiency of the packaging model, and are suitable for electronic equipment and industrial equipment that require efficient heat dissipation. 3D printing technology can achieve fast and precise manufacturing, reduce manufacturing costs, and improve production efficiency. There are various choices of printing materials such as PLA, ABS, and nylon. Suitable materials can be selected according to specific application scenarios. At the same time, the addition of high thermal conductivity materials further enriches the performance and application range of the packaging model. There are many advantages in making packaging models using printing materials such as PLA, ABS, and nylon doped with high thermal conductivity materials, including material property advantages, high thermal conductivity material advantages, and comprehensive advantages. These advantages make the packaging model have broad application prospects in electronic equipment, industrial equipment and other fields.
[0032] In addition, 3D printing technology can accurately manufacture packaging models with complex shapes and structures, providing great flexibility and precision for the preparation of gel phase change heat storage structures.
[0033] In step S2, a PVA aqueous solution containing a hydrated inorganic salt is filled into the packaging mold by vacuuming to perform the first packaging; the mass fraction of PVA in the PVA aqueous solution is 5% - 20%.
[0034] For example, the PVA aqueous solution is filled into the encapsulation model under vacuum conditions to avoid the generation of bubbles and ensure the uniformity and integrity of the filling. The freeze-thaw molding process causes water molecules to form ice crystals and rearrange, thereby forming a stable three-dimensional network structure, which gives the hydrogel excellent mechanical properties and heat storage properties.
[0035] In some specific embodiments, the mass fraction of PVA is selected from 5% - 10%, 15% - 20%, 10% - 15%, 7% -14%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.
[0036] As an example, the hydrated inorganic salt includes one or more of sodium sulfate decahydrate, calcium chloride hexahydrate, and disodium hydrogen sulfate dodecahydrate. These hydrated inorganic salts generally have good solubility and can be uniformly dissolved in the PVA aqueous solution to form a stable solution system. Partially hydrated inorganic salts (such as sodium sulfate decahydrate) have strong hygroscopicity, which helps to adjust the humidity inside the packaging model and maintain the stability of the environment. These hydrated inorganic salts will lose crystal water during heating, but usually will not decompose or produce harmful substances, ensuring the safety of the packaging process. The addition of hydrated inorganic salts can interact with PVA molecules, enhance the mechanical strength of the packaging material, and make it more durable. After losing crystal water, partially hydrated inorganic salts (such as calcium chloride hexahydrate) can form a more stable inorganic skeleton and improve the heat resistance of the packaging material. The hygroscopicity of hydrated inorganic salts helps to adjust the humidity inside the packaging model to prevent performance degradation or damage caused by excessive or low humidity. Partially hydrated inorganic salts (such as disodium hydrogen sulfate dodecahydrate) can be used as pH regulators to keep the pH value inside the encapsulation model within an appropriate range and ensure the stability and performance of the encapsulation material. The addition of hydrated inorganic salts can improve the fluidity of the PVA aqueous solution, making it easier to fill it into the encapsulation model by vacuuming, thereby improving the filling efficiency and encapsulation quality. The addition of hydrated inorganic salts can also reduce bubbles and defects generated during the encapsulation process and improve the integrity and reliability of the encapsulation model.
[0037] Exemplarily, the phase change principle of the above-mentioned complex gel phase change heat storage structure of the present application is mainly based on the latent heat characteristics of phase change energy storage materials (PCM). Phase change energy storage materials can absorb or release a large amount of heat during the phase change process, while the temperature remains almost unchanged. This characteristic makes PCM an effective thermal control material. During the phase change process, PCM stores or releases heat by changing its physical state (such as solid to liquid or liquid to solid).
[0038] In step S3, the encapsulated model after the first encapsulation is freeze-thawed to form a PVA hydrogel; including: freezing the encapsulated model after the first encapsulation at -20°C for 10 h, thawing at 25°C for 2 h, and cycling the freezing and thawing operations 3 to 7 times until the PVA hydrogel is formed.
[0039] In the above scheme, in step S3, the process of freeze-thawing the encapsulated model after the first encapsulation to form a PVA (polyvinyl alcohol) hydrogel is mainly based on the physical cross-linking properties of polyvinyl alcohol and its structural changes during the freezing and thawing process. The formation of polyvinyl alcohol hydrogel mainly depends on the physical cross-linking between its molecular chains. During the freezing process, water gradually solidifies into ice crystals, and the formation of these ice crystals helps to "tighten" the polyvinyl alcohol molecular chains and arrange them in a more orderly manner. During thawing, the ice crystals melt, but the interaction between the polyvinyl alcohol molecular chains has been strengthened, thus forming a stable hydrogel structure. Through multiple freezing and thawing cycles, the interaction between the polyvinyl alcohol molecular chains is further strengthened, forming a more dense and stable hydrogel network structure. This structural change gives the PVA hydrogel better mechanical strength and stability.
[0040] Furthermore, by using the above means, after multiple freeze-thaw cycles, more physical cross-linking points are formed between the molecular chains of the PVA hydrogel, thereby improving its mechanical strength. This enables the PVA hydrogel to withstand greater external forces in practical applications and is not easy to break or deform. Maintain biocompatibility: Polyvinyl alcohol is a hydrophilic polymer with good biocompatibility. The PVA hydrogel formed by physical cross-linking does not introduce any harmful chemicals, thus maintaining its original biocompatibility. This makes PVA hydrogel have broad application prospects in the biomedical field, such as as a tissue engineering material, a drug sustained-release carrier, etc.
[0041] Furthermore, the present application can achieve precise control of the PVA hydrogel structure by adjusting the number of freeze-thaw cycles, freezing and thawing temperature and time and other parameters. This controllable molding process enables PVA hydrogel to meet the requirements of material properties in different application fields. Compared with the traditional chemical crosslinking method, the physical crosslinking method does not need to introduce any chemical crosslinking agent or catalyst, thereby simplifying the preparation process and reducing production costs. Therefore, the process of forming PVA hydrogel by performing multiple freeze-thaw cycle treatments on the encapsulated model after the first encapsulation has the advantages of improving mechanical strength, maintaining biocompatibility, controllable molding process and simplifying the preparation process.
[0042] In some specific embodiments, the number of cycles is determined according to the conditions of hydrogel formation, and can be 3 to 7 times, such as 3 times, 4 times, 5 times, 6 times, or 7 times.
[0043] In step S4, a high thermal conductivity elastomer is filled into the surface of the packaging model after the PVA hydrogel is formed, and secondary packaging is performed, including: fully mixing the silicone rubber and the high thermal conductivity material to form a high thermal conductivity elastomer; before the high thermal conductivity elastomer is cured, immersing the packaging model containing the PVA hydrogel into the high thermal conductivity elastomer, and packaging the surface of the packaging model to form a high thermal conductivity elastomer packaging layer.
[0044] For example, the high thermal conductivity elastomer material has good thermal conductivity and elasticity, which can ensure that heat is efficiently transferred to the external environment and maintain the overall strength of the structure. The secondary packaging process not only improves the stability of the structure, but also enhances its reliability and durability in practical applications.
[0045] In some specific embodiments, the high thermal conductivity elastomer is silicone rubber doped with a high thermal conductivity material, and the high thermal conductivity material is one or more of metal particles, liquid metal, carbon nanotubes, carbon fibers, and graphene.
[0046] In some specific embodiments, the filling rate of the packaging model is variable, the wall thickness of the packaging model is less than 1 mm, and the thickness of the high thermal conductivity elastomer packaging layer is less than 1 mm.
[0047] In the present application, since the phase change energy storage material is a functional material with high energy storage and high energy saving, hydrated salt is a type of inorganic phase change energy storage material with high energy storage density and high thermal conductivity. It stores and releases energy by absorbing and releasing heat during melting and crystallization. Combining it with hydrogel can form phase change heat storage water gel, which can serve as the basis for the application of phase change devices.
[0048] The phase change principle of the complex gel phase change heat storage structure of this application is: hydrogel is the main phase change energy storage material (PCM). When the hydrogel is heated, the water molecules inside it begin to vibrate and absorb heat. As the temperature rises, the hydrogen bonds between the water molecules gradually break, causing the hydrogel to change from solid to liquid (or liquid-like), and absorb a large amount of heat in the process. Conversely, when the hydrogel cools, the liquid water molecules reform hydrogen bonds and change to solid, while releasing the previously absorbed heat.
[0049] Furthermore, the addition of hydrated inorganic salts can affect the phase transition temperature and latent heat value of the hydrogel. By adjusting the type and concentration of hydrated inorganic salts, the phase transition characteristics of the hydrogel can be customized to meet specific application requirements. Hydrated inorganic salts can also enhance the thermal stability and mechanical properties of the hydrogel, allowing it to maintain structural integrity during the phase transition process.
[0050] Furthermore, as a secondary packaging material, the high thermal conductivity elastomer has excellent thermal conductivity. It can efficiently transfer the heat absorbed or released by the hydrogel during the phase change process to the external environment. The elastic properties of the high thermal conductivity elastomer can also ensure the stability and durability of the packaging structure under thermal stress.
[0051] Therefore, the phase change principle of the complex gel phase change heat storage structure is based on the latent heat characteristics of PCM and the interaction between hydrogel, hydrated inorganic salt and high thermal conductivity elastomer. The structure stores and releases heat by precisely controlling the phase change process, thereby achieving effective management and control of temperature.
[0052] The second object of the present invention is to provide a complex gel phase change heat storage structure, which is prepared according to the above-mentioned complex gel phase change heat storage structure preparation method.
[0053] In the complex gel phase change heat storage structure, when a higher temperature liquid flows through, it absorbs part of the heat in the liquid for storage. The specific principle of this process involves the latent heat characteristics of the phase change energy storage material and the thermal conduction and phase change mechanism of the hydrogel. Phase change energy storage materials can absorb or release a large amount of heat during the phase change process, while the temperature remains almost unchanged. This is the latent heat characteristic of PCM and is also the basis for it to be used as a thermal control material. In the above scheme, hydrogel, as the main PCM, will undergo a phase change when heated, from solid to liquid (or liquid-like), and absorb heat in the process.
[0054] Among them, hydrogel has excellent thermal conductivity and can effectively transfer heat from high-temperature areas to low-temperature areas. When a higher-temperature liquid flows through, the hydrogel will quickly absorb the heat in the liquid and transfer the heat to the entire gel structure through its internal heat conduction mechanism. As heat is transferred and accumulated, some areas in the hydrogel will reach their phase transition temperature. At this time, the hydrogel will undergo a phase change from solid to liquid (or liquid-like), and absorb a large amount of heat in the process. This phase change process enables the hydrogel to effectively store heat from high-temperature liquids.
[0055] In some embodiments, when the hydrogel absorbs enough heat and undergoes a phase change, a large amount of thermal energy is stored inside it. This thermal energy can be released when needed through appropriate conditions (such as lowering the ambient temperature or applying external pressure), thereby realizing the heat storage and release functions. In a complex gel phase change heat storage structure, when a higher temperature liquid flows through, it uses the thermal conduction and phase change mechanism of the hydrogel to absorb the heat in the liquid and store it. This process is based on the latent heat characteristics of PCM and the unique properties of the hydrogel, achieving effective management and control of heat.
[0056] The following describes the invention in conjunction with specific embodiments.
[0057] Example 1 This embodiment provides a method for preparing a complex gel phase change heat storage structure by 3D printing. Figure 1 The encapsulation model is shown, and then the PVA aqueous solution containing hydrated inorganic salts is filled into the encapsulation model by vacuuming, and then it is freeze-thawed to form, and finally the surface of the encapsulation model is encapsulated again with a high thermal conductive elastomer. The above preparation process includes the following steps: Step 1: Use 3D printing to print Figure 1 For the package model shown, the filling rate is set to 20% to make the package model have sufficient strength, the wall thickness of the package model is set to 0.1mm to make it easier for the PVA solution to be drawn into the package model, and PLA is selected as the printing material.
[0058] Step 2: Prepare a 10% PVA aqueous solution, add sodium sulfate decahydrate of the same mass as PVA and stir evenly, and then infiltrate the PVA aqueous solution containing hydrated inorganic salts into the encapsulation model under the action of atmospheric pressure by vacuuming.
[0059] Step 3: Freeze the encapsulation model into which the PVA aqueous solution containing hydrated inorganic salts is drawn at -20°C for 10 h, thaw at 25°C for 2 h, and repeat the freezing and thawing operation 7 times until a PVA hydrogel is formed.
[0060] Step 4: The silicone rubber and the high thermal conductivity material are fully mixed with a stirring rod to form a high thermal conductivity elastomer as a packaging material, and the packaging model containing the PVA hydrogel is immersed in the high thermal conductivity elastomer before the high thermal conductivity elastomer is cured, and then the excess high thermal conductivity elastomer on the surface of the packaging model is removed to make the thickness of the packaged high thermal conductivity elastomer less than 1 mm, and the high thermal conductivity elastomer is completely cured under natural conditions to form a Figures 2 to 4 The complex gel phase change heat storage structure shown.
[0061] in, Figures 2 to 4 A specific complex gel phase change heat storage structure is provided, comprising a phase change heat storage body 1 having an inlet 3 and an outlet 4 , a fluid channel 2 inside the phase change heat storage body 1 , and the fluid channel 2 is connected to both the inlet 3 and the outlet 4 .
[0062] More specifically, the fluid channels 2 are arranged in a serpentine shape in the phase change heat storage body 1 to be in more uniform contact with the hydrogel.
[0063] When a liquid with a relatively high temperature flows through the fluid channel 2, the phase change heat storage body 1 will absorb part of the heat therein for heat storage.
[0064] Example 2 This embodiment provides a method for preparing a complex gel phase change heat storage structure, and the preparation process includes the following steps: Step 1: Use 3D printing to print Figure 1 For the package model shown, the filling rate is set to 22% to make the package model have sufficient strength, the wall thickness of the package model is set to 0.2mm to make it easier to draw the PVA solution into the package model, and ABS is selected as the printing material.
[0065] Step 2: Prepare a 5% PVA aqueous solution, add calcium chloride hexahydrate of the same mass as PVA and stir evenly, and then infiltrate the PVA aqueous solution containing hydrated inorganic salts into the encapsulation model under the action of atmospheric pressure by vacuuming.
[0066] Step 3: Freeze the encapsulation model into which the PVA aqueous solution containing hydrated inorganic salts is drawn at -25°C for 8 hours, thaw at 20°C for 3 hours, and repeat the freezing and thawing operation 5 times until a PVA hydrogel is formed.
[0067] Step 4: The silicone rubber and the high thermal conductivity material are fully mixed with a stirring rod to form a high thermal conductivity elastomer as a packaging material, and the packaging model containing the PVA hydrogel is immersed in the high thermal conductivity elastomer before the high thermal conductivity elastomer is cured, and then the excess high thermal conductivity elastomer on the surface of the packaging model is removed, so that the thickness of the packaged high thermal conductivity elastomer is less than 1 mm, specifically 0.8 mm; wait for the high thermal conductivity elastomer to completely cure under natural conditions to form a similar Figures 2 to 4 The complex gel phase change heat storage structure shown.
[0068] Example 3 This embodiment provides a method for preparing a complex gel phase change heat storage structure, and the preparation process includes the following steps: Step 1: Use 3D printing to print Figure 1 The packaging model shown in the figure has a filling rate of 18% to make the packaging model have sufficient strength, and a wall thickness of 0.8 mm to make it easier for the PVA solution to be drawn into the packaging model. Nylon is selected as the printing material.
[0069] Step 2: Prepare a PVA aqueous solution with a mass fraction of 20%, add sodium sulfate decahydrate with an equal mass of PVA thereto and stir evenly, and then infiltrate the PVA aqueous solution containing hydrated inorganic salts into the encapsulation model under the action of atmospheric pressure by vacuuming.
[0070] Step 3: Freeze the encapsulation model into which the PVA aqueous solution containing hydrated inorganic salts is drawn at -18°C for 12 h, thaw at 26°C for 1.5 h, and repeat the freezing and thawing operation three times until a PVA hydrogel is formed.
[0071] Step 4: The silicone rubber and the high thermal conductivity material are fully mixed with a stirring rod to form a high thermal conductivity elastomer as a packaging material. Before the high thermal conductivity elastomer is cured, the packaging model containing the PVA hydrogel is immersed in it, and then the excess high thermal conductivity elastomer on the surface of the packaging model is removed, so that the thickness of the packaged high thermal conductivity elastomer is less than 1 mm, and the actual thickness is 0.5 mm. Wait for the high thermal conductivity elastomer to be completely cured under natural conditions to form a similar Figures 2 to 4 The complex gel phase change heat storage structure shown.
[0072] Example 4 This embodiment provides a method for preparing a complex gel phase change heat storage structure, and the preparation process includes the following steps: Step 1: Use 3D printing to print Figure 1 For the package model shown, the filling rate is set to 22% to make the package model have sufficient strength, the wall thickness of the package model is set to 0.7 mm to make it easier for the PVA solution to be drawn into the package model, and PLA is selected as the printing material.
[0073] Step 2: Prepare a PVA aqueous solution with a mass fraction of 8%, add calcium chloride hexahydrate with an equal mass of PVA thereto and stir evenly, and then infiltrate the PVA aqueous solution containing hydrated inorganic salts into the encapsulation model under the action of atmospheric pressure by vacuuming.
[0074] Step 3: Freeze the encapsulation model into which the PVA aqueous solution containing hydrated inorganic salts is drawn at -23°C for 11 h, thaw at 24°C for 2.5 h, and repeat the freezing and thawing operation 5 times until a PVA hydrogel is formed.
[0075] Step 4: The silicone rubber and the high thermal conductivity material are fully mixed with a stirring rod to form a high thermal conductivity elastomer as a packaging material. Before the high thermal conductivity elastomer is cured, the packaging model containing the PVA hydrogel is immersed in it, and then the excess high thermal conductivity elastomer on the surface of the packaging model is removed, so that the thickness of the packaged high thermal conductivity elastomer is less than 1 mm, and the actual thickness is 0.9 mm. Wait for the high thermal conductivity elastomer to be completely cured under natural conditions to form a similar Figures 2 to 4 The complex gel phase change heat storage structure shown.
[0076] certainly, Figures 2 to 4 The complex gel phase change heat storage structure shown is only an example and is not limited to a specific structure. The complex gel phase change heat storage structure can be designed into other shapes that meet the needs according to actual applications.
[0077] Example 5 This embodiment provides a method for preparing a complex gel phase change heat storage structure, and the preparation process includes the following steps: Step 1: Use 3D printing to print Figure 1 The packaging model shown in the figure has a filling rate of 18% to make the packaging model have sufficient strength, and a wall thickness of 0.8 mm to make it easier for the PVA solution to be drawn into the packaging model. Nylon is selected as the printing material.
[0078] Step 2: Prepare a PVA aqueous solution with a mass fraction of 20%, add disodium hydrogen sulfate dodecahydrate with an equal mass of PVA thereto and stir evenly, and then infiltrate the PVA aqueous solution containing hydrated inorganic salts into the encapsulation model under the action of atmospheric pressure by vacuuming.
[0079] Step 3: Freeze the encapsulation model into which the PVA aqueous solution containing hydrated inorganic salts is drawn at -24°C for 10 h, thaw at 23°C for 2 h, and repeat the freezing and thawing operation 4 times until a PVA hydrogel is formed.
[0080] Step 4: The silicone rubber and the high thermal conductivity material are fully mixed with a stirring rod to form a high thermal conductivity elastomer as a packaging material. Before the high thermal conductivity elastomer is cured, the packaging model containing the PVA hydrogel is immersed in it, and then the excess high thermal conductivity elastomer on the surface of the packaging model is removed, so that the thickness of the packaged high thermal conductivity elastomer is less than 1 mm, and the actual thickness is 0.5 mm. Wait for the high thermal conductivity elastomer to be completely cured under natural conditions to form a similar Figures 2 to 4 The complex gel phase change heat storage structure shown.
[0081] In order to verify the temperature control performance of complex gel phase change thermal storage structure, such as Figure 5 As shown in the figure, five complex gel phase change heat storage structures were prepared. The corresponding packaging model filling rates of the complex gel phase change heat storage structures were 22%, 20%, 18%, 22%, and 18%, and the PVA mass fractions were 5%, 10%, 20%, 8%, and 8%, respectively. The five complex gel phase change heat storage structures were placed in a high and low temperature test chamber for cooling and heating tests. The test environment temperature range was -40 o C to 0 o C. The constant temperature and heat storage characteristics of the complex gel phase change heat storage structure were studied by monitoring the temperature of the center point inside. Figure 5 The temperature variation trend of the center of the complex gel phase change heat storage structure is shown. Figure 5 It can be seen that for -20 o C to -10 o The complex gel phase change heat storage structure at a specific temperature has heat storage performance. In two cooling-heating cycle tests, the temperature change trend of the center point of the complex gel phase change heat storage structure remains consistent, verifying the repeatability of the experiment.
[0082] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a complex gel phase change heat storage structure, characterized in that: The steps include: Provide packaging model; Filling the PVA aqueous solution containing hydrated inorganic salt into the packaging mold by vacuuming to perform the first packaging; The encapsulated model after the first encapsulation is subjected to freeze-thaw molding to form a PVA hydrogel; Filling a high thermal conductive elastomer onto the surface of the encapsulation model after the PVA hydrogel is formed for secondary encapsulation; After waiting for the high thermal conductivity elastomer to completely solidify, a complex gel phase change heat storage structure is obtained.
2. According to claim 1, a method for preparing a complex gel phase change heat storage structure is characterized in that: The packaging model provided is a packaging model with a set heat storage structure shape printed by 3D printing, and the filling rate of the packaging model is 18%~22%.
3. The method for preparing a complex gel phase change heat storage structure according to claim 1, characterized in that: The material of the packaging model is a printing material doped with a high thermal conductivity material, and the printing material is one or more of PLA, ABS, and nylon; the high thermal conductivity material is one or more of carbon nanotubes, carbon fibers, and graphene.
4. The method for preparing a complex gel phase change heat storage structure according to claim 1, characterized in that: The mass fraction of PVA in the PVA aqueous solution is 5% - 20%.
5. The method for preparing a complex gel phase change heat storage structure according to claim 1, characterized in that: The hydrated inorganic salt includes one or more of sodium sulfate decahydrate, calcium chloride hexahydrate, and disodium hydrogen sulfate dodecahydrate, and the added amount of the hydrated inorganic salt is the same as that of PVA.
6. The method for preparing a complex gel phase change heat storage structure according to claim 1, characterized in that: The freeze-thaw molding of the packaging model after the first packaging comprises: The encapsulated model after the first encapsulation was frozen at -18~-25℃ for 8~12 h, thawed at 20~26℃ for 1~3 h, and the freezing and thawing operation was repeated 3 to 7 times until the PVA hydrogel was formed.
7. The method for preparing a complex gel phase change heat storage structure according to claim 1, characterized in that: The high thermal conductivity elastomer is silicone rubber doped with a high thermal conductivity material, and the high thermal conductivity material is one or more of metal particles, liquid metal, carbon nanotubes, carbon fibers, and graphene.
8. The method for preparing a complex gel phase change heat storage structure according to claim 1, characterized in that: The method of filling the high thermal conductive elastomer into the surface of the encapsulation model after the PVA hydrogel is formed comprises: The silicone rubber and the high thermal conductivity material are fully mixed to form a high thermal conductivity elastomer; before the high thermal conductivity elastomer is cured, the packaging model containing the PVA hydrogel is immersed in the high thermal conductivity elastomer, and the surface of the packaging model is packaged to form a high thermal conductivity elastomer packaging layer.
9. The method for preparing a complex gel phase change heat storage structure according to claim 1, characterized in that: The filling rate of the packaging model is variable, the wall thickness of the packaging model is less than 1 mm, and the thickness of the high thermal conductivity elastomer packaging layer is less than 1 mm.
10. A complex gel phase change heat storage structure, characterized in that: It is prepared according to the method for preparing a complex gel phase change heat storage structure according to any one of claims 1 to 9.
Citation Information
Patent Citations
Discretization preparation method of two-dimensional material aerogel with designable three-dimensional structure
CN113289558A
Flexible attachable thermal management / electromagnetic shielding composite material and preparation method thereof
CN115678499A
Preparation method of foam liquid metal flexible radiator
CN116481367A
Preparation method of composite phase change energy storage material with multi-dimensional heat conduction path and device
CN117511513A
Hierarchically Structured Hydrogel with Tunable Mechanical Properties
US20230331937A1